Taxonomy of the ant genus Carebara Westwood (Formicidae, Myrmicinae) in the Malagasy Region - Azorsa, Frank (Zookeys, 2018)
Abstract. The genus Carebara is revised for the Malagasy region, and based on the examination of over 10,000 specimens, twenty-three species are recognized. Twenty one of these are described as new (C. bara sp. n., C. berivelo sp. n., C. betsi sp. n., C. creolei sp. n., C. demeter sp. n., C. dota sp. n., C. hainteny sp. n., C. hiragasy sp. n., C. jajoby sp. n., C. kabosy sp. n., C. lova sp. n., C. mahafaly sp. n., C. malagasy sp. n., C. omasi sp. n., C. placida sp. n., C. raberi sp. n., C. salegi sp. n., C. sampi sp. n., C. tana sp. n., C. tanana sp. n., C. vazimba sp. n.), and two are redescribed, C. grandidieri Forel (= C. voeltzkowi Forel n. syn.) and C. nosindambo Forel. A lectotype is designated for C. nosindambo. C. creolei sp. n. is known only from Mauritius and Seychelles, C. grandidieri Forel is distributed in Comoros, Madagascar and Mayotte, and the other twenty-one species are endemic to Madagascar. Most of the Carebara species recorded in this work are endemic to a specific habitat (ecoregion), but some of them (C. bara sp. n., C. grandidieri Forel, C. jajoby sp. n., C. kabosy sp. n., and C. nosindambo Forel) are widespread within Madagascar across all major habitats. The worker caste of Carebara can be differentiated from other genera in the Myrmicinae subfamily by the presence of the following combination of characters: antennae of eight to eleven segments, with a two-segmented club; anterior clypeal margin without central isolated seta (rarely present in some species or specimens), and usually with four distinct setae; mandibles with four to seven teeth (except in one species from Ghana - C. crigensis with three teeth); and palp formula 2,2 or 1,2. We report that almost all Carebara species found in the Malagasy region have intermediates (distinct forms) in the major worker subcaste, with the largest major workers showing remnants of queen flight sclerites and ocelli. The widespread presence of intermediates in the major worker subcaste expands the morphological boundaries of Carebara. We present an overview of the natural history of Carebara in the Malagasy region, an illustrated key for the identification of the known Malagasy species of Carebara, as well as high-resolution images and distribution maps. Unique identifiers are used for all specimens studied, including type material, and the raw data that forms the basis of this study are available on www.antweb.org (open access).